2016
DOI: 10.1016/j.jallcom.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation strengthening in titanium microalloyed high-strength steel plates with new generation-thermomechanical controlled processing (NG-TMCP)

Abstract: We elucidate here the strengthening mechanisms in titanium microalloyed low-carbon steels, which were rolled into plates of 12 mm thickness using a combination of thermomechanical controlled processing (TMCP) and ultrafast cooling (UFC). The ultrafast cooling combined with thermomechanical controlled processing is referred by us as new generation (NG)-TMCP. Chemical phase analysis, small-angle X-ray scattering (SAXS) and high-resolution transmission electron microscopy (TEM) were used to study the characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…They incorporated a formula for obtaining crack susceptibility in terms of units of crack susceptibility (UCS), in function of the composition of the welded metal: This formula is valid in the following composition ranges: 0.08-0.23% C 0.010-0.050% S 0.010-0.045% P 0.15-0.65% Si 0.45-1.6 Mn 0-0.07% Nb They concluded that there is no risk of cracking in compositions above the following compositions: HSLA steels have been widely used for their excellent properties obtained through their microstructure, which is strongly altered by the selection of alloying elements and thermomechanical processes. [113]. In the year 2007, Bose-Filho et al studied the effect of Ti, Ni, Mo and Cr on the microstructural development in the welding of an HSLA steel and reported that increasing the Ti content from 50 to 400 ppm does not contribute considerably to microstructural development; however, by increasing the content of Ni, Mo and Cr to increase the hardenability, they observed a change in the microstructural morphology from a mixture of allotriomorphic ferrite, Widmanstätten ferrite, acicular ferrite and microphases to a mixture of acicular ferrite, bainite, low carbon martensite and microphases [114].…”
Section: Microalloyed Steels Weldingmentioning
confidence: 99%
“…They incorporated a formula for obtaining crack susceptibility in terms of units of crack susceptibility (UCS), in function of the composition of the welded metal: This formula is valid in the following composition ranges: 0.08-0.23% C 0.010-0.050% S 0.010-0.045% P 0.15-0.65% Si 0.45-1.6 Mn 0-0.07% Nb They concluded that there is no risk of cracking in compositions above the following compositions: HSLA steels have been widely used for their excellent properties obtained through their microstructure, which is strongly altered by the selection of alloying elements and thermomechanical processes. [113]. In the year 2007, Bose-Filho et al studied the effect of Ti, Ni, Mo and Cr on the microstructural development in the welding of an HSLA steel and reported that increasing the Ti content from 50 to 400 ppm does not contribute considerably to microstructural development; however, by increasing the content of Ni, Mo and Cr to increase the hardenability, they observed a change in the microstructural morphology from a mixture of allotriomorphic ferrite, Widmanstätten ferrite, acicular ferrite and microphases to a mixture of acicular ferrite, bainite, low carbon martensite and microphases [114].…”
Section: Microalloyed Steels Weldingmentioning
confidence: 99%
“…Precipitation strengthening plays an important role in the design and fabrication of advanced structure materials with superior mechanical properties and strong resistance to radiation damage [1][2][3][4][5][6][7][8]. With increasing unprecedented environmental challenges, advanced ultra-high strength steels strengthened by nanoscale precipitates have been developed [9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the application of ultra-fast cooling of laboratory vacuum melted 0.15C-0.08Ti-27ppmN steels, to obtain a mixture of TiC and Fe3C in a bainitic microstructure was studied by Li et al 227 with the same aim as Fu et al .212 After roughing,one sequence consisted of rolling in the recrystallization temperature zone,1150-1096°C,further rolling in the non-recrystallization temperature zone, finishing at 864°C, then water cooling at 64°Cs -1 through the γ → α transformation region to 580°C, followed by an isothermal holding for 20 min, prior to air cooling to RT. A fully bainitic microstructure was observed in the 12mm thick plate.Besides nanoscale TiC particles,a high volume fraction of cementite, ≤ 35nm was observed,which , it was claimed made a greater contribution to σy of ~690 MPa, than the TiC particles.This is a similar conclusion to that of Mao.…”
Section: The Above Discussion Have Involved Multiple Precipitation Omentioning
confidence: 99%